INFESTATION OF Dolops discoidalis (CRUSTACEA: BRANCHIURA) IN Pseudoplatystoma punctifer (SILURIFORMES: PIMELODIDAE), Colossoma macropomum (CHARACIFORMES: SERRASALMIDAE) AND Brochis multiradiatus (SILURIFORMES: CALLICHTHYIDAE) - URIBE CHUQUIVAL, Karla Leslie (2020)
This study was carried out at the facilities of the “Centro de Investigaciones Fernando Alcántara Bocanegra (CIFAB) of the “Instituto de Investigaciones de la Amazonía Peruana (IIAP), Iquitos; with the objective of knowing the parasitic behavior of Dolops discoidalis (Bouvier, 1899) (Crustacea: Branchiura) in three fish species. The sampling was carried out during the months of November and December 2018. For this study, individuals of this parasitic species were extracted from the body surface of adult specimens of Pseudoplatystoma punctifer (Castelnau, 1855), bred in captivity at the CIFAB facilities. The collected parasites were taken to the laboratory of “Parasitología y Sanidad Acuícola” of the institute (IIAP) to perform two experiments evaluating the parasitic behavior of D. discoidalis in three fish species: P. punctifer, Colossoma macropomum (Cuvier, 1816) and Brochis multiradiatus (Orcés V., 1960). Experiment I consisted of placing one specimen of each species of fish in a glass aquarium (4 replications) and distributing 18 specimens of D. discoidalis per experimental unit in order to determine the parasitic behavior of this species. For experiment II, 2 specimens of C. macropomum were placed in two different aquariums and 4 specimens of B. multiradiatus in one aquarium, with 11 parasites in each of the experimental units. The results of Experiment I showed all individuals of D. discoidalis only parasitized P. punctifer, revealing a marked affinity for this species. In Experiment II it was observed that D. discoidalis, in the absence of P. punctifer, is capable of parasitizing C. macropomum and B. multiradiatus specimens, detecting between 1 to 2 parasites per parasitized fish, revealing very low affinity. Histological studies are recommended to determine the degree of damage caused by this parasite in fish, mainly in P. punctifer, a species that showed high susceptibility to D. discoidalis.